An Evaluation of Barriers and Facilitators for a Pressure Injury Prevention Link Nurse Role: A Mixed-Methods Study in New Zealand. Issue 4 (July 2022) - Moir, Chris; Taylor, Peta; Seaton, Philippa; Snell, Helen
Abstract : PURPOSE: The purpose of this study was to identify barriers and facilitators for nurses in a pressure injury prevention (PIP) link nurse role. DESIGN: Mixed-methods study that used nominal group technique with focus groups, followed by online surveys. SAMPLE AND SETTING: The PIP link nurse project recruited 52 RNs; 32 completed the PIP educational program and participated in data collection. The sample was drawn from PIP link nurses, who were invited to participate in focus groups at the end of the project to identify perceived facilitators and barriers to their role. Focus groups were specific to work areas: aged care and community visiting, and hospital. Two were in an urban setting and one in a rural environment. Twenty-two PIP link nurses participated across 3 groups. To ensure comprehensive data from all involved in the project, online surveys were created using focus group priorities as the basis for questions to send to all PIP link nurses, their managers, and workplace colleagues. METHODS: Participants were invited to participate in focus groups to identify perceived facilitators and barriers to their role. These focus groups were organized around care settings: aged care, community visiting, and hospital. Using a nominal group technique focus group process, participants were asked to identify barriers and facilitators to their role. These were shared with the group until all answers were declared and understood. Voting on order of priority then took place, with majority voting leading to a prioritized list of facilitators and barriers for each group. Considering the similarities and differences across group priorities, researchers developed online surveys representing the main facilitators and barriers from the focus groups. Surveys were then distributed to all PIP link nurses, their managers, and colleagues. Survey data were collected and analyzed in REDCap and reported as percentages of agreement to the questions for each group of respondents. RESULTS: Focus group data indicated facilitating priorities included PIP link nurses' commitment to the role, the support they received from their managers and colleagues, and time release to complete the role. Barriers included lack of time—when other work pressures took priority, and PIP link nurses felt the focus on applying quality improvement theory was more challenging than they had anticipated. Surveys from all groups reiterated the importance of the support of the workplace team in facilitating the role, and the time pressures for the PIP link nurse were a barrier to the role. CONCLUSION: While the funding of such projects is advantageous, it should be carefully and generously considered how much time is required if the project is to succeed so that lack of time to complete the role does not become a barrier to successful completion.